Remediation of Cu in the Contaminated Soil by Using Equisetum debile (Horsetail)* - Irna Rahmaniar; Idris Maxdoni Kamil (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Paddy fields in the Rancaekek area, Bandung Regency-Indonesia, has been contaminated by textile wastewater. The area needs to recover back to its normal condition and function. Several compounds were found in the soil, such as Cu, Zn, Pb, Cd, Co, Ni, and Cr. Phytoremediation was selected as a site remediation strategy, which employs plants to remove non-volatile and immiscible soil contents. The objective of the study was to determine the ability of Equisetum debile to absorb Cu from the contaminated soil. Cu measurement was conducted by using the AAS (Atomic Absorption Spectrophotometer) method. The study has shown that Equisetum debile can absorb Cu concentrations of up to 25.3 ppm in 60 days after initial planting. However, the Enrichment Coefficient value (0.392) indicated that Equisetum debile was not efficient as a hyperaccumulator plant.